ECOLE: a pedagogical environment for non procedural languages - Zegour, D. E. (2007)
The work described in this paper is related to three areas in the programming world : logic, functional and object programming. The main objective is essentially pedagogical since it is question here to make a synthesis on non procedural languages. To achieve this, we have considered many construction types, each one represents the one of evoked programming. Many fully-documented environments have been developed for writing constructions of any type, transforming them in order to evaluate them by showing the work really accomplished in the least detail.